DMLess: uma abordagem para gerenciamento de dados em ambientes serverless - Santos, João Paulo Vital (2022)
Serverless computing is a technology trend aimed at providing transparent elasticity and millisecond billing model. However, this computing model requires major technological changes, especially in DBMSs, as in the serverless environment all functions have maximum duration, fixed amount of memory and no persistent local storage. Furthermore, there is a trade-off between latency and cost that must be considered when using serverless platforms. To overcome these limitations, this work presents the DMLess data management approach that exploits the memory capacity and elasticity of serverless platforms, combining different types of storage to reduce latency and costs. Experimental results have shown that DMLess offers performance and cost that could compete with off-the-shelf storage solutions.